A simple mixed-micelle process for selective microextraction of trace Th(IV) from lanthanide matrices - Abou El-Reash, Yasmeen G.; Algethami, Faisal K.; Alotaibi, Abdullah N.; Hashem, M. A.; Wahba, M. G.; Ismail, M. A.; Keshta, Basem E.; Hosseini-Bandegharaei, Ahmad (Frontiers in Water, 2025)
Prolonged exposure to thorium and its compounds can cause severe and irreversible damage to the bones and the kidneys, highlighting the need for its selective separation from other rare earth elements, particularly uranium. Traditional detection methods for Th(IV) are often time-consuming and costly. In this study, we present a simple and efficient mixed micelle-mediated microextraction method for Th(IV). Thorium was complexed with Solochrome Cyanine R (SCR) and extracted using Triton X-114 at 45 °C with KNO₃ and cetyltrimethylammonium bromide (CTAB) to enhance phase separation and extraction efficiency. The method achieved >95% extraction efficiency, a 100-fold preconcentration factor, and a detection limit of 0.8 ng mL−1. Thorium was completely extracted at pH ≥ 3 in the presence of U(VI) and lanthanides (Nd(III), Ce(III), and Gd(III)). Recovery experiments with reference materials, freshwater, and synthetic mixtures confirmed the accuracy and applicability of the method.